OR-HPB-05: Long-term outcomes after endoscopic ultrasonography-guided ablation of pancreatic cysts - Choi, Jun-Ho (Endosc Ultrasound, 2017)
OBJECTIVES: The aim of this study was to investigate the long-term outcomes after endoscopic ultrasonography (EUS)-guided pancreatic cyst ablation. METHODS: In a single-center, prospective study, 164 patients with pancreatic cysts underwent EUS-guided cyst ablation using ethanol with paclitaxel. The inclusion criteria were as follows: unilocular or oligolocular cysts, clinically indeterminate cysts that required EUS fine-needle aspiration, and/or cysts that grew during the observation period. Treatment response was classified as complete resolution (CR), partial resolution (PR), or persistent cyst, with <5%, 5%–25%, and 25% of the original cyst volume, respectively. RESULTS: The median largest diameter of the cyst was 32 mm and the median volume was 17.1 mL. Based on cyst fluid analysis, there were 71 mucinous cystic neoplasms, 16 serous cystic neoplasms, 11 intraductal papillary mucinous neoplasms, 3 pseudocysts, and 63 indeterminate cysts. Sixteen treated patients (9.8%) had adverse events (severe 1, moderate 4, and mild 11). Treatment response was as follows: CR, 114 (72.2%); PR, 31 (19.6%); and persistent cysts, 13 (8.2%). Twelve of 13 patients with persistent cysts underwent surgery. During clinical and imaging follow-up (median 72 months, interquartile range 50–85 months) of the 114 patients with CR, only two patients (1.7%) showed cyst recurrence. Based on multivariate analysis, the absence of septa (odds ratio [OR], 7.12; 95% confidence interval [CI], 2.72–18.67) and cyst size <35 mm (OR, 2.39; 95% CI, 1.11–5.16) predicted CR. CONCLUSION: Among patients with pancreatic cysts who achieved CR after EUS-guided cyst ablation, 98.3% remain in remission at 6-year follow-up. Unilocular and small cyst was predictive of CR.